From flexible to subtitling: Exploring students’ experiences on improving listening skills through podcast - Andayani, Widya; Perangin-angin, Alemina Br.; Tambunan, Anna Riana Suryanti; Sari, Winda Setia (JOALL (Journal of Applied Linguistics and Literature), 2024)
English language learning is mandatory at all levels of school in Indonesia. When acquiring proficiency in the English language, learners frequently experience many challenges, particularly in the domains of speaking and listening. Hence, the researcher examined this matter through the implementation of a study utilizing the Podcast functionality within the Spotify application. One advantage of utilizing this application is its potential to enhance listening proficiency in the context of English language acquisition. Furthermore, its user-friendly interface enables convenient access and utilization at any given time and location. The present study was undertaken on a cohort of German language education students over the years 2020 and 2021. The chosen study methodology involves conducting interviews via the Zoom program, wherein a series of questions are compiled for the participants. The investigation yielded diverse perspectives. In order to enhance their English language proficiency, students must consistently engage in regular practice of speaking and listening activities that are directly relevant to the process of learning the English language. Similar to one's leisure time, it is imperative to utilize available time for the sake of ongoing learning. The study highlights the importance of consistent practice in speaking and listening activities to enhance English language proficiency among students learning English as a foreign language.